PENINGKATAN HASIL BELAJAR BIOLOGI SISWA MELALUI PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF MAKE A MATCH PADA KONSEP REPRODUKSI MANUSIA DI KELAS IX B SMP NEGERI 2 PANGSID - Ali, Hamdah (bionature, 2010)
This research is a Classroom Action Research which was performed in two cycles.The research was intended to know the improvement of Students? Biology learning result through Make a Match Cooperative learning model. The subject of the research was 31 students of IX B class at SMPN 2 Pangsid in the academic year 2008/2009. The data was collected through observation, test, and documentation. The results shown that  learning  biology through Make a Match cooperative learning model could improve the learning outcomes of the student significantly. Before the application of the model the students? learning outcome got only 50 on average, but after the last cycle applied the outcome achieved 78,55. The score was above the Minimal criteria 70. Therefore it can be concluded that the Make a Match cooperative learning model at IX class SMPN 2 Pangsid can improve the students learning result especially on Human Reproduction concept. Besides that,  the research also found out that the students got encouragement to study and to think postively toward the lesson within the process of the research.